Development and characterization of eco-friendly non-isocyanate urethane monomer from Jatropha curcas oil for wood composite applications - Bhakri, Samsul; Muhammad Ghozali; Cahyono, Edy; Triwulandari, Evi; Restu, Witta Kartika; Solihat, Nissa Nurfajrin; Iswanto, Apri Heri; Antov, Petar; Savov, Viktor; Lee, Seng Hua; Agustiany, Erika Ayu; Kristak, Lubos; et al. (Tech Science Press, 2022)
The aim of this research work was to evaluate the potential of using renewable natural feedstock, i.e., Jatropha curcas oil (JCO) for the synthesis of non-isocyanate polyurethane (NIPU) resin for wood composite applications. Commercial polyurethane (PU) is synthesized through a polycondensation reaction between isocyanate and polyol. However, utilizing toxic and unsustainable isocyanates for obtaining PU could contribute to negative impacts on the environment and human health. Therefore, the development of PU from eco-friendly and sustainable resources without the isocyanate route is required. In this work, tetra-n-butyl ammonium bromide was used as the activator to open the epoxy ring with 3-Aminopropyltriethoxisylane as a catalyst to yield urethane of JCO (UJCO). The UJCO were characterized by Fourier Transform Infra-Red spectroscopy (FTIR) and their oxirane, and hydroxyl values were measured. The result showed that a decrease in oxirane value was found while the hydroxyl value was increased during the time, confirming that the urethane group was formed. The presence of functional groups in FTIR spectra at wave numbers 1732.08, 1562.34, and 3348.42 cm−1 indicates the functional groups of C = O (urethane carbonyl), –NH, and –OH, respectively confirmed this finding. The potential applications of NIPU in the wood composite were also outlined.